A forward model for earthquake generation on interacting faults including tectonics, fluids, and stress transfer - Fitzenz, Delphine D.; Miller, Stephen Andrew (My University, 2001)
We present a forward model of interacting faults for systems of any geometry. The model generalizes that of Miller et al. [1996,1999] to a fully three-dimensional model where faults of any strike and geometry interact through an elastic matrix using the general solutions of Okada [1992]. The model includes large-scale plate motion loading and increasing pore pressures from a source term, undrained poroelastic effects, large coseismic hydraulic property changes, and porosity creation through dilatant slip. To illustrate the basic behavior and utility of the model, results are presented of the long-term evolution (approximate to 9300 years) for a generic case of a blind, dipping fault and a subvertical strike-slip fault in a transpressional environment. We show the stress state evolution along both faults, seismicity time lines, quasi-static rupture propagation including rake angle changes, local and regional stress buildup and rotations, static and dynamic fault interactions, and Delta CFS (changes in Coulomb Failure Stress) within the fault system. Large compartments of varying overpressure result on both faults from coseismic pore pressure changes and contribute to the complexity of the stress state. For the considered case, we find that the poroelastic effects on the receiver fault are about twice the change in the shear stress, providing a significant contribution to the Delta CFS. Regional stress rotations in response to the model seismicity indicate that further model developments must include dynamic generation of new faults in response to the evolving tectonic regime.